PENYALAHGUNAAN MINUMAN KERAS OLEH REMAJA DI DESA KARANG TUNGGAL KECAMATAN PARENGGEAN KABUPATEN KOTAWARINGIN TIMUR - Arifudin Arifudin (Journal SOSIOLOGI, 2019)
In this day and age it can be said that the era is very modern with the era of technology that is growing rapidly, associations are increasingly free, so that young people easily access information they want and are wrong in mingling, mostly juvenile delinquency in Karang Tunggal Village, Parenggean District East Kotawaringin Regency is consuming liquor. This study aims to determine what motivation and how the realm, capital and pratice of adolescents in consuming liquor. Based on the type of data the research approach used in this study is a qualitative approach. The quality approach is expected to be more integrated into the problem so that it can understand the phenomena that occur within the community. In addition, a qualitative approach is expected to reveal the existing problem situations in Karang Tunggal Village, Parenggean District, East Kotawaringin Regency. The data sources used in this study are primary data in the form of interviews with 5 teenagers who consume liquor and secondary data obtained from documents and archives related to research. Data collection techniques used by researchers are direct observation, interviews and documentation. And data analysis techniques that researchers use are data reduction, data presentation and drawing conclusions done carefully by verifying in the form of a review of field notes so that the existing data is tested in accordance with the theory used. The results of this study indicate that adolescents in Karang Tunggal have the motivation to consume liquor as a form of solidarity with friends, which they often hold binge drinking together. Then fortunately holding a real liquor party is one of the most important factors, to hold a liquor party in need of capital to hold liquor and the practice is that they do it repeatedly and generate habit among the teenagers.